Micro-cathcment rain water harvesting technology in conservation agriculture and plant production - Kuzucu , Meryem; Gökçen, Ibrahim Samet (Bangladesh Journal of Botany, 2024)
Water harvesting techniques provide collecting rainwater to reduce water shortage effects and drought as well as added soil and water conservation benefits in dry areas. In the present study, drought effects and flood disasters on agriculture and rainwater harvesting benefits were examined in Southeastern Anatolia region of Turkey. Results showed that, runoff loss was found higher in the plots of plastic mulch than the plots of stone mulch. Sediment loss was found maximum in the plots of the surface compaction whereas minimum losses were quantified in the stone plots. Best erosion control was observed for micro-catchment surface covered with plastic sheet. As a result, Negarim micro-catchment water harvesting technique was found to be useful and feasible technique in enhancing the plant production and the conservation of natural resources. Bangladesh J. Bot. 53(1): 9-16, 2024 (March)